A non-human hepadnaviral adjuvant for hepatitis C virus-based genetic vaccines. Issue 25 (27th May 2016) - Levander, Sepideh; Sällberg, Matti; Ahlén, Gustaf; Frelin, Lars
Highlights: Hepatitis C virus (HCV) is the major causative agent for severe liver disease and cancer. No prophylactic or therapeutic vaccines are available but highly effective antivirals. Herein a genetic vaccine was evaluated for immunogenicity. New molecular adjuvants and delivery techniques significantly improved immunogenicity. This technology can most likely be universally expanded to other genetic vaccines. Abstract: Human hepatitis B virus (HBV) core antigen (HBcAg) can act as an adjuvant in hepatitis C virus (HCV)-based DNA vaccines. Since two billion people are, or have been, in contact with HBV, one may question the use of human HBV sequences as adjuvant. We herein evaluated non-human stork hepatitis B virus core gene-sequences from stork as DNA vaccine adjuvants. Full-length and fragmented stork HBcAg gene-sequences were added to an HCV non-structural (NS) 3/4A gene (NS3/4A-stork-HBcAg). This resulted in an enhanced priming of HCV-specific IFN-γ and IL-2 responses in both wild-type (wt)- and NS3/4A-transgenic (Tg) mice, the latter with dysfunctional NS3/4A-specific T cells. The NS3/4A-stork-HBcAg vaccine primed NS3/4A-specific T cells in hepatitis B e antigen (HBeAg)-Tg mice with dysfunctional T cells to HBcAg and HBeAg. Repeated immunizations boosted expansion of IFN-γ and IL-2-producing NS3/4A-specific T cells in wt- and NS3/4A-Tg mice. Importantly, NS3/4A-stork-HBcAg-DNA induced in vivo long-term functional memory T cell responses, whose maintenance required CD4 + T cells. Thus, avian HBcAg gene-sequences from stork can effectively act as a DNA vaccine adjuvant. This technology can most likely be universally expanded to other genetic vaccine antigens, as this completely avoids the use of sequences from a human virus where a pre-existing immunity may interfere with its adjuvant effect.